Organizational Leadership and Supervision of Islamic Education at MTsN 10 Bireuen - Ilwan Ilwan; Faisal Ali; Fakri Fakri; Asmak Asmak (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study discusses organizational leadership management. Supervision of Islamic education at MTsN 10 Bireuen is the primary objective of implementing leadership and supervision within the educational components, such as leadership motivation, efforts to foster motivation, supervision and development of MTsN 10 Bireuen teachers, and supervision within Islamic education at MTsN 10 Bireuen. Islamic education in the modern era must integrate organizational leadership and supervision, maintaining fundamental Islamic values and adopting new methods and approaches relevant to the current context. Islamic educational institutions, particularly MTsN 10 Bireuen, need to adopt various leadership and supervision methods to improve the quality of human resources, including the principal's approach to teacher supervision and development through three methods: academic, directive, and clinical supervision. This study employed a qualitative field study method, focusing on teacher career development management at MTsN 10 B